Accidental diagnosis of significant coronary artery disease by cardiac CT scan to rule out left atrial appendage thrombus in patients with atrial fibrillation during COVID19 pandemic. (4th February 2022) - Szedlacsek, Z; Herczku, F; Kozma, I; Vertesaljai, M; Andreka, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction The exclusion of left atrial appendage (LAA) thrombus prior to urgent electrical cardioversion (DCCV) for atrial fibrillation (AF) is traditionally performed by transesophageal echocardiography (TEE). During the COVID19 pandemic, TEE was replaced by cardiac CT (CCT) due to its high aerosol generating property, which in addition to assessing the anatomy of the heart, can also be used to evaluate the coronary arteries at the same time. Methods In our retrospective study, we evaluated the cardiac CT scans of patients undergoing DCCV in our institution between January 1, 2020 and February 28, 2021 for coronary artery disease (CAD). The scans were performed by a GE Revolution 256-slice CT scanner. Results CCT scans were performed in 32 patients to rule out LAA thrombus (24 male; 8 female; age: 61.8 ± 11.2 years; BMI: 29.2 ± 4.4; heart rate: 79.2 ± 24.4 1/min; CHA2DS2VASc score: 2.4 ± 1.5). The mean radiation exposure of the scans was DLP: 356.3 ± 130.1 mGy-cm; effective dose: 5.0 ±1.8 mSv, Ca-score: 361.4 ± 883.0. In 4 equivocal cases TEE was also performed with negative results. No CAD was confirmed in 7 cases, mild CAD in 14 patients. CCT was not diagnostic only in 4 cases. Significant (moderate or severe) CAD was detected in 7 cases, invasive coronary angiography (ICA) was also performed in 5 cases. In 2 cases significant one-vessel disease, in 2 other cases borderline (FFR: 0.81 and 0.84) stenosis and in 1 case only mild CAD was diagnosed by ICA. Conclusions: CCT scans performed by our 256-slice CT scanner for AF can identify patients, who require further invasive or invasive and functional coronary artery assessment with satisfactory accuracy. In terms of coronary artery disease, the non-diagnostic scan rate was low, despite the presence of arrhythmia, suboptimal heart rate and higher than usual Ca-score.